Some recent German fairy tales - Needham, Lucy (My University, 1908)
Introduction: The following stories are translations from “New German Fairy Stories” (Neuerdeutscher Marchenschatz 7te Sonderheft der Woche) published by August Scherl, Berlin. This collection consists of the best thirty stories among over four thousand presented in a story writing contest.
Citation: Needham, Lucy. Some recent German fairy tales. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Fairy Tales; German Literature; Translations; Handwritten; Graduating theses; Senior theses; Theses